2022
DOI: 10.3390/microorganisms10030655
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Bifidobacterium asteroides Isolates

Abstract: Bifidobacteria have long been recognized as bacteria with probiotic and therapeutic features. The aim of this work is to characterize the Bifidobacterium asteroides BA15 and BA17 strains, isolated from honeybee gut, to evaluate its safety for human use. An in-depth assessment was carried out on safety properties (antibiotic resistance profiling, β-hemolytic, DNase and gelatinase activities and virulence factor presence) and other properties (antimicrobial activity, auto-aggregation, co-aggregation and hydropho… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 74 publications
0
7
0
Order By: Relevance
“…The function of probiotics to modulate intestinal microbiota and intestinal disease has been studied [ 59 ]. Due to their specific adaptations, probiotics can compete with other microorganisms, leading to alteration and modulation of the gut microbiota [ 60 ]. Moreover, probiotics can replace, adhere to and colonize with intestinal epithelial cells [ 61 ].…”
Section: Discussionmentioning
confidence: 99%
“…The function of probiotics to modulate intestinal microbiota and intestinal disease has been studied [ 59 ]. Due to their specific adaptations, probiotics can compete with other microorganisms, leading to alteration and modulation of the gut microbiota [ 60 ]. Moreover, probiotics can replace, adhere to and colonize with intestinal epithelial cells [ 61 ].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, 98 putative virulence genes of 15 strains with whole genome analysis were detected in a study examining bifidobacteria causing bacteremia. 66 On the other hand, Pino et al 67 reported the absence of asa1, gelE, cylA, esp, and hyl genes for Bifidobacterium asteroides BA15 and BA17 strains. It is not possible to make a detailed comparison since there are limited studies on the virulence genes of Bifidobacterium spp.…”
Section: Hemolytic and Dnase Activitymentioning
confidence: 99%
“…Bifidobacterium : Bifidobacterium is another commensal probiotic bacterium that participates in the homeostasis of the gut microorganism community ( 86 ). Bifidobacterium , the dominant species in the large intestine, requires an anaerobic environment ( 78 ).…”
Section: Culturing Ios With Microorganisms To Study Host-microbiome I...mentioning
confidence: 99%